When Organization Studies Turns to Societal Problems: The Contribution of Marxist Grand Theory. Issue 4 (April 2015) - Vidal, Matt; Adler, Paul; Delbridge, Rick
Marxist theory, we argue, can be a valuable resource as organization studies turns to the urgent societal problems of our times. In order to address these problems, organizational studies needs greater historical depth and interdisciplinarity. We argue that these imperatives necessitate a return to grand theory. Grand theories provide the frameworks needed for integrating in a systematic as opposed to an ad hoc manner both scholarship across disciplines and middle-range theories within disciplines. We show that marxism offers a particularly fruitful grand theory for organization studies and for the social sciences more broadly, because it affords a platform for integrating various social sciences and because it offers penetrating insight into both the longue durée of history and the political-economic dynamics of capitalism. In making our case, we present and defend the core ideas of marxism, including its theory of modes of production, its distinctive theory of "soft" technological and economic determinism, its labor theory of value, and its account of the key developmental tendencies of capitalism—concentration and centralization of capital, socialization, and recurrent crises. We illustrate the power of these ideas by showing how they can be used to enrich organizational research on the 2007-8 financial crisis. And we introduce the four articles in this Special Themed Section, which show the capacity of marxist concepts to reframe and enrich research on traditional and emerging topics in organization studies, including organizational learning and communities of practice, knowledge work, teamwork and collaboration, social media and digital capitalism, and organizational routines and path dependence.